Simulation of reactive distillation for biodiesel production from Jatropha Curcas seed oil - Mohd Usman, Mohd Junaidi (2010)
Reactive distillation column (RD column) is a hybrid equipment that combines two of major equipment, i.e. reactor and distillation column. RD column brings many advantages to the chemical industries especially in reducing the cost of building plant, and energy consumption. Biodiesel is an excellent substitute for conventional diesel fuel because of being renewable, nontoxic and biodegradable. In the biodiesel industry, mainly for the biodiesel production from Jatropha Curcas seed oil (JCO oil); the reactive distillation is still being a new technology. The JCO oil contains high percentage of triolein and oleic acid which are really useful for engine performance. This study is mainly based on simulation method by using Aspen Plus 12.1 software. The biodiesel routes process used is triglyceride hydrolysis and fatty acid esterification process. This study will focus on oleic acid esterification with methanol in the reactive distillation column to produce methyl oleate. The simulation was done in equilibrium stage model incorporate with kinetic of reaction model using RADFRAC unit as the RD column model. The purpose of the simulation carried out is to determine the effect of important parameters, i.e. reflux ratio, column pressure, feed temperature, etc, that affect the RD column performance and design the optimized RD column condition to achieve highest product conversion. In the nutshell, the optimum parameters for simulated RD column are; reflux ratio 0.01, feed temperature at 363.15K @ 900C, column pressure at 100 kPa, 14 stages with 6 reactive stages, and oleic acid and methanol feed locations, accordingly, at 3nd stage and 8th stage, to achieve 99.65% of oleic acid conversion to biodiesel.